Psychometric properties of the motor diagnostics in the German football talent identification and development programme - Höner, O.; Votteler, A.; Schmid, M.; Schultz, F.; Roth, K. (Journal of Sports Sciences, 2015)
The utilisation of motor performance tests for talent identification in youth sports is discussed intensively in talent research. This article examines the reliability, differential stability and validity of the motor diagnostics conducted nationwide by the German football talent identification and development programme and provides reference values for a standardised interpretation of the diagnostics results. Highly selected players (the top 4% of their age groups, U12-U15) took part in the diagnostics at 17 measurement points between spring 2004 and spring 2012 (N = 68,158). The heterogeneous test battery measured speed abilities and football-specific technical skills (sprint, agility, dribbling, ball control, shooting, juggling). For all measurement points, the overall score and the speed tests showed high internal consistency, high test-retest reliability and satisfying differential stability. The diagnostics demonstrated satisfying factorial-related validity with plausible and stable loadings on the two empirical factors "speed" and "technical skills". The score, and the technical skills dribbling and juggling, differentiated the most among players of different performance levels and thus showed the highest criterion-related validity. Satisfactory psychometric properties for the diagnostics are an important prerequisite for a scientifically sound rating of players` actual motor performance and for the future examination of the prognostic validity for success in adulthood.